Spatial patterns of caddisflies from Austral South America - Dos Santos, Daniel Andrés (2015)
Trichoptera are relevant members of the freshwater benthos that can exploit a broad variety of habitats. We explored their distribution patterns in Austral South America using a network quantitative approach applied on point occurrence data. The primary goal was to recognize groups of species connected by strong links of sympatry and secondarily to evaluate the structure of the sympatry network (patterns of connectivity) at higher taxonomic levels. We compiled 2,522 geographic points associated with 446 species. The strength of sympatry links were inferred directly from dot maps. Using the taxonomic resolution of species, we identified two major groups of co-occurring species that mimic in a geographic context the classic zoogeographic division of the study area: the Andean–Patagonian complex (of “cold-adapted” organisms) versus the Extra-Andean domain (of “warm-adapted” organisms) spanning the subtropical belt of the region. Within these major divisions, groups of highly co-distributed species were also found which in turn show a variety of overlapping spatial configurations. Overlap was centred at the following pivoting areas: Yungas of NW Argentina, Paranaense forest of NE Argentina and Valdivian temperate forest of Patagonia. Three very interesting findings emerged from the analyses: (i) Sierras Centrales of Córdoba correspond to the southern portion of many subtropical elements occurring in NW Argentina, (ii) some elements fit the disjunction between NW and NE Argentina and (iii) Uruguay is more closely related to NE Argentina than to Buenos Aires, suggesting that the Pampas region (Uruguay + Buenos Aires) could be an ill-defined biogeographic entity. Patterns at the species level become progressively blurred in going upward through the hierarchical classification.